Atretic Cephalocele. Issue 3 (September 2022) - Bennett, Mónica; Costa, Sofia; Almeida, Ricardo; Castelo, Rui; Costa, José Augusto
Brain ultrasonography of a male newborn of unremarkable term gestation and prenatal ultrasonography, with a soft tissue pedicle protruding from the parieto-occipital region, covered by skin, confirmed the skull defect, and communication with the intracranial space and the magnetic resonance imaging confirmed the presence of a 4, 6 cm cystic structure, without brain tissue. Atretic cephaloceles are a rare neural tube defects and in most of the cases are not associated with other central nervous system abnormalities. The majority of patients have a good prognosis.